Diagnosis of elevated intracranial pressure in critically ill adults: systematic review and meta-analysis. (24th July 2019) - Fernando, Shannon M; Tran, Alexandre; Cheng, Wei; Rochwerg, Bram; Taljaard, Monica; Kyeremanteng, Kwadwo; English, Shane W; Sekhon, Mypinder S; Griesdale, Donald E G; Dowlatshahi, Dar; McCredie, Victoria A; Wijdicks, Eelco F M; et al.
Abstract: Objectives: To summarise and compare the accuracy of physical examination, computed tomography (CT), sonography of the optic nerve sheath diameter (ONSD), and transcranial Doppler pulsatility index (TCD-PI) for the diagnosis of elevated intracranial pressure (ICP) in critically ill patients. Design: Systematic review and meta-analysis. Data sources: Six databases, including Medline, EMBASE, and PubMed, from inception to 1 September 2018. Study selection criteria: English language studies investigating accuracy of physical examination, imaging, or non-invasive tests among critically ill patients. The reference standard was ICP of 20 mm Hg or more using invasive ICP monitoring, or intraoperative diagnosis of raised ICP. Data extraction: Two reviewers independently extracted data and assessed study quality using the quality assessment of diagnostic accuracy studies tool. Summary estimates were generated using a hierarchical summary receiver operating characteristic (ROC) model. Results: 40 studies (n=5123) were included. Of physical examination signs, pooled sensitivity and specificity for increased ICP were 28.2% (95% confidence interval 16.0% to 44.8%) and 85.9% (74.9% to 92.5%) for pupillary dilation, respectively; 54.3% (36.6% to 71.0%) and 63.6% (46.5% to 77.8%) for posturing; and 75.8% (62.4% to 85.5%) and 39.9% (26.9% to 54.5%) for Glasgow coma scale of 8 or less. Among CT findings, sensitivity and specificity were 85.9% (58.0% to 96.4%) and 61.0% (29.1% to 85.6%) for compression of basal cisterns, respectively; 80.9% (64.3% to 90.9%) and 42.7% (24.0% to 63.7%) for any midline shift; and 20.7% (13.0% to 31.3%) and 89.2% (77.5% to 95.2%) for midline shift of at least 10 mm. The pooled area under the ROC (AUROC) curve for ONSD sonography was 0.94 (0.91 to 0.96). Patient level data from studies using TCD-PI showed poor performance for detecting raised ICP (AUROC for individual studies ranging from 0.55 to 0.72). Conclusions: Absence of any one physical examination feature is not sufficient to rule out elevated ICP. Substantial midline shift could suggest elevated ICP, but the absence of shift cannot rule it out. ONSD sonography might have use, but further studies are needed. Suspicion of elevated ICP could necessitate treatment and transfer, regardless of individual non-invasive tests. Registration: PROSPERO CRD42018105642.